Effect of nicotine on secretory component synthesis by secretory epithelial cells. - Gregory, R L (1996)
Previously, we reported that secretory component (SC), lactoferrin (LF), and lysozyme (LY) levels were significantly lower in saliva from smokeless tobacco (ST) users than in saliva from control non-tobacco users. However, the levels of salivary immunoglobulin A were significantly higher, albeit with an altered attachment of SC, in ST users than in control subjects. SC, LF, and LY are synthesized by secretory epithelial cells at mucosal sites adjacent to lymphocyte regions. In the present report, HT-29 human epithelial cells, cultured with various concentrations of an ST aqueous extract or pure nicotine (0 to 1 mg/ml) or cotinine (0 to 5 mg/ml), exhibited significantly lower levels of cell-associated cell lysate (CL) and secreted culture supernatant (CS) SC, LF, and LY than cells cultured without ST components. Nicotine significantly decreased (P < or = 0.05) the synthesis of SC by 20 to 100%, LF by 20 to 60%, and LY by 5 to 75% of CL and CS control values. Studies also indicated significant decreases (P < or = 0.05) in SC, LF, and LY levels in both CL and CS of cells cultured with ST aqueous extract or cotinine. Total cell numbers and metabolic activity significantly decreased primarily when cells were incubated with higher concentrations of ST extract, nicotine, or cotinine. The addition of human recombinant interleukin-4 or gamma interferon diminished the effects ST had on HT-29 cell synthesis of SC, LF, and LY. Our data indicate that nicotine, cotinine, and ST have an adverse effect on synthesis and secretion of SC, LF, and LY. These effects were below ST concentrations found to be cytotoxic for secretory epithelial cells. Furthermore, addition of interleukin-4 or gamma interferon reduced the suppressive effect of ST on synthesis or secretion of SC, LF, or LY.